Introduction to energy analysis - Blok, Kornelis; Nieuwlaar, Evert (New York: Routledge, 2021)
"This textbook provides an introduction to energy analysis for those students who want to specialise in this challenging field. In comparison to other textbooks, this book provides a balanced treatment of complete energy systems, covering the demand side, the supply side, and the energy markets that connect these. The emphasis is very much on presenting a range of tools and methodologies that will help students find their way in analysing real world problems in energy systems. This new edition has been updated throughout and contains additional content on energy transitions and improvements in the treatment of several energy systems analysis approaches. Featuring learning objectives, further readings and practical exercises in each chapter, Introduction to Energy Analysis will be essential reading for upper-level undergraduate and postgraduate students with a background in the natural sciences and engineering. This book may also be useful for professionals dealing with energy issues, as a first introduction into the field"--
Includes bibliographical references and index.
Keywords: Power resources; Energy conservation; Energy transfer